INVESTIGATING BANKING HOUSEHOLDS' DEPOSITS USING VECTOR AUTOREGRESSIVE MODEL VAR - DĂNULEȚIU, Adina Elena; IUGA, Iulia Cristina; SOCOL, Adela (Annales Universitatis Apulensis Series Oeconomica, 2014)
Nowadays, settling a proper and adequate relationship with the customers became a concern of the banks, that have to "back to basics" and obtain the trust when interact with customers. Banking customers represented by the population's householders matter in banks' financing if we retain that in the last year, the household deposits represented 29.2% of total liabilities of credit institutions active in Romania. This paper argues that in order to study the influence factors that affect the banking customers' behavior, it is important to consider the saving process of banking customers as an exogenous dynamic phenomenon, while the study does not deny, but it not approached another face of thinks - the endogenous influences. The paper examines if there exist any long-run relationships between deposits made by the population's householders and their behavior influenced by the interest rate on the deposits set up in banks by householders, the unemployment rate, the monthly net wages in the economy and the consumer price index. We provide an unrestricted Vector Autoregression Model (VAR) in order to investigate the relationship between variables mentioned above, using the data set on Romanian banking system, which covers the period January 2007 - December 2012. Our research confirms the impact that the interest rate on deposits has on the banking customers' behavior, mirrored in the deposits made with active banks in Romania by the population's householders.